Are attention-deficit/hyperactivity disorder symptoms associated with negative health outcomes in individuals with psychotic experiences? Findings from a cross-sectional study in Japan - Stickley, Andrew; Shirama, Aya; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2023)
Objective Although research has indicated that the prevalence of attention-deficit/hyperactivity disorder (ADHD) may be elevated in individuals with psychotic disorders, as yet, there has been comparatively little research on this association and its effects among adults at the subclinical level. To address this deficit, the current study examined the association between psychotic experiences (PE) and ADHD symptoms in Japanese individuals and whether the presence of ADHD symptoms increases the risk for negative health outcomes in people with PE. Method Data were analyzed from an online sample of 1,452 individuals (age 18–89; 51.5% female) collected in 2021. Information on PE was obtained with the PRIME Screen-Revised (PS-R), while the Adult ADHD Self-Report Scale (ASRS) Screener was used to measure ADHD symptoms. Information was also obtained on a number of health outcomes including anxiety and depressive symptoms and suicidal ideation. Logistic regression was used to assess associations. Results In a fully adjusted analysis PE were associated with almost three times higher odds for ADHD symptoms (OR: 2.92, 95%CI: 1.19–7.17). In an analysis that was restricted to individuals with PE, ADHD symptoms were associated with significantly increased odds for depressive symptoms, lifetime suicidal ideation, perceived stress and severe sleep problems. Conclusion ADHD symptoms are present in some individuals with PE and increase the odds for several detrimental health outcomes in this population. Identifying co-occurring PE and ADHD/ADHD symptoms may facilitate treatment options and help prevent negative health outcomes in individuals with these conditions.